Which type of instruction fosters chunk learning? Preliminary conclusions - Mercedes Pérez Serrano (Revista de Lingüística y Lenguas Aplicadas)
Formulaic language learning has been shown to be problematic and slow in adult L2 learners. In this study, we test some of the recommendations of a Lexical Approach. We compare the results of the implementation of chunk attention-directing techniques and explicit exercises of previously selected collocations in 52 Spanish as a second language learners over a period of seven weeks. In light of the results obtained, we can conclude that (1) exposure to lexical chunks, chunk noticing in the input and explicit exercises contribute to the development of abilities in the active recognition of chunks, and (2) learning gains obtained through explicit exercises are significantly greater than those obtained through attention-directing techniques.